The Influence of Occupational Health and Safety (K3) Attitudes and Behavior (K3) on the Work Productivity of Employees of Fish Processing Craftsmen on the Coast of Demak Regency - Hardani Widhiastuti; Rusmalia Dewi; Rosalia T. Gabronino; Rebecca Maquiling (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This research was conducted in order to participate in resolving the problems that occur in UMKM Processed Mina in the coastal areas of Central Java, especially the Sayung area. Many fish processing businesses in the area only pursue profits to help the household economy, considering that their business productivity has not developed/increased, which is likely due to a lack of attention to conscious efforts to carry out or comply with Occupational Health and Safety (K3), such as using personal protective equipment such as hand straps, boots, or in processing fish related to stoves, there are no manual extinguishers for home businesses. K3 attitudes and behaviors for those whose workers are mostly women, are not/may not yet aware of this. Efforts to foster K3 attitudes and behaviors are things that affect economic businesses, especially mina because productivity is increasing. The results of the study are expected to help the local village government to strive to improve their business.